Languages and conforming tax avoidance: The roles of corruption and public governance - Muhammad Faisal; Sidharta Utama; Dahlia Sari; Arifin Rosid (Cogent Business & Management, 2023)
This paper investigates the empirical relationship between language structures and prevalent tax avoidance practices, specifically focusing on the influence of linguistic future time reference (FTR) on conforming tax avoidance. It also explores how corruption and public governance modulate this relationship. This study uses a cross-country analysis of 33 sample countries. The empirical evidence obtained shows that conforming tax avoidance is mostly practiced by companies in countries whose grammar requires speakers to give signs related to future events (Strong Future Time References/Strong FTR) than companies in countries that do not require speakers to give related signs future (Weak Future Time References/Weak FTR). This study also found that low levels of corruption and strong public governance played a role in suppressing high conforming tax avoidance behavior in countries with strong FTR speakers. These insights underscore the significance of national anti-corruption efforts and governance structures. Policymakers should consider these socio-cultural and institutional factors when addressing corporate tax avoidance. This research augments accounting, economics, and finance discourses by integrating linguistics-a perspective often overlooked.
Keywords: D73; H26; H70; M41; Z10; 650; conforming; conforming tax avoidance; corruption; future time reference; languages; public governance; tax avoidance